Efektivitas Pembatasan Sosial Berskala Besar di Wilayah Kabupaten Tangerang Berdasarkan Peraturan Pemerintah Nomor 21 Tahun 2020 Tentang Pembatasan Sosial Berskala Besar dalam Rangka Percepatan Penanganan Corona Virus Disease 2019 - Bilal Syahdin; Mohamad Fasyehhudin (Fakultas Hukum Universitas Sultan Ageng Tirtayasa, 2021)
Indonesia is a constitutional state based on the provisions of Article 1 paragraph (3) of the 1945 Constitution of the Republic of Indonesia which reads that the State of Indonesia is a constitutional state. The Indonesian government issued a policy for the response to the Covid-19 Pandemic disaster, namely by ratifying Government Regulation Number 21 of 2020 concerning Large-Scale Social Restrictions in the Context of Accelerating the Handling of Corona Virus Disease 2019 (Covid-19). This is the background for the imposition of large-scale social restrictions in the Tangerang Regency area in early March 2020, with 43 confirmed Covid-19 cases and 468 suspected Covid-19 cases. The Government of Tagerang Regency has proposed large-scale social restrictions to the Minister of Health and this has been approved by the Minister of Health with the Decree of the Minister of Health Number. HK.01.07 / MENKES / 249/2020. Researchers are interested in examining the effectiveness of large-scale social restrictions in the Tangerang Regency area based on Government Regulation Number 21 of 2020 concerning Large-Scale Social Restrictions in the Context of Accelerating the Handling of Corona Virus Disease 2019 (Covid-19)? and What is the social impact of large-scale social restrictions in the Tangerang Regency area on the handling of Covid-19?This research uses normative juridical and sociological empirical methods, using descriptive analytical research. Using primary data sourced from the field in the form of interviews with the Tangerang Regency Office and the Tangerang Regency Covid-19 Handling Task Force, secondary data sourced from laws, official documents, and books related to the object of research. Data collection techniques using library research and field research in the form of direct interviews. As well as data analysis using qualitative juridical analysis using the data obtained and analyzed in the form of sentences.Based on research data, the author can be obtained through direct interviews with the Tangerang District Health Office and the Covid-19 Handling Task Force which should be in large-scale social restrictions, the Tangerang Regency government should socialize and apply strict sanctions and rules in accordance with the Tangerang Regent Regulation, so that the public can discipline to do 3M, namely washing hands, maintaining distance, and wearing masks and not violating health protocols.